Productivity of arabica coffee plants under influence of population density north-west fluminense - Andrade, Wander Eustáquio de Bastos; Guimarães, Paulo Tácito Gontijo; Faquin, Valdemar; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2014)
The objective of this work was to evaluate different arrangements of population (distances between rows x distances between plants in the row) in the productivity in the coffee plants (Coffea arabica) in North West Fluminense. The variety was Catuai Vermelho IAC 144, the experimental design was a randomized complete block, with four replicates, in splitplot. Four distances between rows (1,0, 1,5, 2,0 e 2,5 m) were used in the plot and four distances between plants in the row (0,25, 0,50, 0,75 e 1,00 m) in the subplot. The test was evaluated in the period 2004 - 2011 (eight outputs) by analyzing the cumulative production in bags of coffee per hectare benefited by means of the production biennia. The results were submitted to analysis individual variance and differences between means were compared by F test at 5% probability, to study through regression. It was observed that the reduction in the distance between the rows and between the plants in the row resulted in increased production eight samples evaluated; that more productive combinations for the same population of plants per hectare occurred when it was used shortest distance between plants and that the same plant but in different arrangements do not provide the same production.